Analisis Hukum Ekonomi Syariah terhadap Manajemen Contract Drafting Pembiayaan Perumahan: Studi Kasus Bank Syariah di Kabupaten Sumedang - Ishma Shafiyatu Sa’diyah; R. Dzihni Jawahir Labib (Penerbit Lestari Sakha Pustaka, 2026)
This study aims to analyze the compliance of housing financing contract drafting management at Islamic banks in Sumedang Regency with the principles of sharia economic law, identify legal problems arising in the contract drafting process, and formulate an ideal contract drafting model based on sharia economic law perspectives. This research employs a qualitative approach with a socio-legal research design. Primary data were collected through in-depth interviews with Islamic bank officials, Sharia Supervisory Board members, notaries, and customers, as well as documentation studies of housing financing contracts. Secondary data were obtained from legislation, DSN-MUI fatwas, and relevant literature. Data analysis was conducted using the Miles and Huberman interactive model with source and method triangulation. The findings reveal that housing financing contract drafting at Islamic banks in Sumedang Regency generally refers to DSN-MUI fatwas and involves the Sharia Supervisory Board in the drafting process. However, several substantive problems were identified: contract formats still adopt conventional bank credit agreement patterns with partial modifications; an imbalance in bargaining positions where all clauses are unilaterally determined by the bank; profit-sharing mechanisms in musyarakah mutanaqishah contracts based on financing percentages rather than actual profits; and price uncertainty issues in istishna contracts potentially containing gharar elements. This study concludes that a reformulation of the contract drafting model is needed to genuinely reflect sharia economic law principles, ensuring transparency, fairness, and equality between parties.